The Nottingham recovery from COVID-19 research platform (NoRCoRP): Functional, clinical and patient-reported outcomes in adults referred to a post-COVID respiratory service - Malik Hamrouni; Ayushman Gupta; Sophie Middleton; Sabrina Prosper; Theresa Harvey-Dunstan; Joanne Porte; Tricia M. McKeever; Ian P. Hall; Charlotte E. Bolton (PLoS ONE, 2026)
Aims To characterise symptoms, function and patient-reported outcome measures (PROMs), and identify associated factors in adults with persisting respiratory symptoms post-COVID. Methods Cross-sectional analysis of 210 non-hospitalised adults referred to a post-COVID respiratory clinic (December 2020-July 2024) who consented to research. Assessments included demographics, symptoms, lung function, chest CT, and several PROMs: MRC dyspnoea score, Nijmegen Questionnaire score (NQ), Hospital Anxiety and Depression Scale, Chalder Fatigue Scale, Short Physical Performance Battery (SPPB) and Fried Frailty Index. Multivariate logistic regression examined key exposure-outcome associations. Results Among participants (mean age 49.4 years; 68% female; median 13.3 months since COVID-19 diagnosis), 95% reported shortness of breath, 54% had clinically significant breathlessness (MRC ≥ 3), 68% had an NQ score (>23) consistent with dysregulated breathing, 32% had a low SPPB score (<10), and 77% were classed as frail/pre-frail, despite the majority being of working age. Nearly half (47%) of those employed pre-infection had not returned to previous hours. Spirometry and CT abnormalities were not common. Higher body mass index (odds ratio = 1.10, 95% confidence interval = 1.05–1.16, n in model = 190) and depression (2.25, 1.13–4.56, n = 164) were associated with MRC ≥ 3. Dysregulated breathing was associated with female sex (3.63, 1.77–7.60, n = 186), current/ex-smoker (2.56, 1.25–5.47, n = 186), fatigue (8.87, 2.59–37.0, n = 162), anxiety (3.57, 1.70–7.69, n = 162) and depression (5.70, 2.59–13.40, n = 162). A low SPPB score was associated with female sex, current smoking, depression, clinically significant breathlessness, dysregulated breathing, and greater deprivation. Conclusion In non-hospitalised patients with persistent respiratory symptoms post-COVID, dysregulated breathing, deconditioning and psychological distress were key factors linked with symptom burden. These findings suggest a multidisciplinary approach should be considered to optimise recovery.